What can I do for you? Appearance and Application of Robots - Lohse, Manja; Hegel, Frank; Swadzba, Agnes; Rohlfing, Katharina; Wachsmuth, Sven; Wrede, Britta (Workshop on The Reign of Catz and Dogz? The role of virtual creatures in a computerised society)
In recent years industrial robots have been successfully established because they fulfil meaningful tasks in production. In contrast the question of applications for social robots is still open. For quite some time they have only been used in research or at best as simple toys by real users in everyday life situations. However, we suggest that there are still unknown application fields that are suitable for existing robots. Therefore, our approach is to show short movies and descriptions of real robots to participants and ask whether there are any specific tasks these robots could perform in the naive users' everyday life. The systems' appearance and abilities strongly influence the user's expectations, that's why we suppose that we will find strong differences between zoomorphic robots like AIBO and iCat and other robots like BIRON (functional design) and BARTHOC (humanoid). We have conducted an online study with more than 100 participants to test this hypothesis.